Francis Bacon's Contribution to the Development of Social Science in the Perspective of the History of Philosophy of Science - Putri, Aulia Rahmi; Fatimah, Siti; Anwar, Syafri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
This study examines the contribution of Francis Bacon's epistemological thinking to the development of modern science and its relevance to the foundation of social science, especially in Social Studies education. The main issue of this research departs from the scientific paradigm shift from the speculative scholastic tradition to a scientific approach based on observation and empirical experience. By using qualitative methods through literature study and historical-philosophical analysis, this research traces how Bacon's inductive method shapes a scientific mindset that is rational, objective, and systematic. The results show that Bacon's principle of empiricism is not only the basis for natural sciences, but also provides a methodological framework for modern social studies. His concept of idola mentis emphasizes the importance of freeing the mind from bias and prejudice in the process of acquiring scientific knowledge. Bacon's thinking is also relevant in the context of modern education through the application of inquiry-based and experiential learning models that encourage students' critical and reflective thinking skills. Although this research is conceptual in nature, the results open new directions for empirical studies that examine the application of Bacon's principles of empiricism in contemporary social research and pedagogy. Thus, Bacon's intellectual legacy affirms the importance of balance between rationality, empirical experience, and moral responsibility in building the progress of science and civilization.